2021
DOI: 10.1177/21582440211008876
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Ability of Emotional Creativity in Creative Performance Among University Students

Abstract: This study investigated the predictive ability of emotional creativity (EC) in creative performance (CP). The sample consisted of 297 male and female students from literary, educational, and administrative specializations. EC was assessed by Averill’s Emotional Creativity Inventory that includes three dimensions: preparedness, novelty, and effectiveness. Mednick’s Remote Associates Test was used to assess CP. Results revealed that the three dimensions of EC predicted CP. Statistically significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The purpose of the current study was to report the relationships between creativity, emotional intelligence, and personality traits (openness to experiences, agreeableness, emotional stability, conscientiousness, and extraversion). Much of the related research has focused on the relationship between emotional intelligence and creativity (Alzoubi et al, 2021; Duman et al, 2014; Ruiz‐Ariza et al, 2019; Stawicki et al, 2023; Stephens et al, 2015; Tu et al, 2020) or personality traits and creativity (Jirásek & Sudzina, 2020; Karwowski et al, 2013; Li et al, 2022; Singh & Kaushik, 2015), and some of them have revealed diverse findings. The intent of the current study is to have a holistic view of the associations among the mentioned variables.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the current study was to report the relationships between creativity, emotional intelligence, and personality traits (openness to experiences, agreeableness, emotional stability, conscientiousness, and extraversion). Much of the related research has focused on the relationship between emotional intelligence and creativity (Alzoubi et al, 2021; Duman et al, 2014; Ruiz‐Ariza et al, 2019; Stawicki et al, 2023; Stephens et al, 2015; Tu et al, 2020) or personality traits and creativity (Jirásek & Sudzina, 2020; Karwowski et al, 2013; Li et al, 2022; Singh & Kaushik, 2015), and some of them have revealed diverse findings. The intent of the current study is to have a holistic view of the associations among the mentioned variables.…”
Section: Discussionmentioning
confidence: 99%
“…Creativity generally supports creative performance and innovations ( Fetrati and Nielsen, 2018 ; Alzoubi et al, 2021 ). However, negative emotions and stress present over the COVID-19 epidemic might have mitigated the impact of creativity on innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Female participants score higher than males on two of those facets: emotional preparedness and effectiveness/authenticity, and those can be mapped approximately to a variety of other personality variables, including the Big Five personality traits. One recent study (Alzoubi et al, 2021) shows that these three facets predict performance creativity, while another study argues they predict intrinsic motivation and academic engagement in university students (Oriol et al, 2016). Second, unrelated to creativity per se, but indirectly relevant, the Empathy Components Questionnaire (ECQ; Batchelder et al, 2017) measures cognitive and affective components of empathy, including ability and drive components within each.…”
Section: Existing Instrumentsmentioning
confidence: 99%